Rancang Bangun Turbin Angin Untuk Pembangkit Listrik Tenaga Angin (Sebagai Alternatif Pembangkit Listrik Daerah Pesisir Pantai) - Wildan Hamdani; Ahmad Yani; Toni Hendrawan. R (Jurnal Teknik Juara Aktif Global Optimis, 2021)
The basic working principle of a wind turbine is to convert mechanical energy from the wind into rotary energy on the blades, the turbine rotation is used to turn a generator to produce electricity. The wind turbine under study is a propeller wind turbine whose axis is placed horizontally. The purpose of this study was to determine the output power produced by the wind turbine. Methods The research was conducted using experimental methods. The results showed that the designed wind turbine was able to produce electrical power at wind speeds of less than 40 m/s, overall based on the research that the maximum power value occurred at 17:00 with a wind speed of 28 m/s the power generated was 0.054 Watt, while the lowest turbine output power occurred at 15:00 with a wind speed of 18 m/s turbine output power of 0.025 Watt.